2004
DOI: 10.2527/2004.8261781x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic exocrine secretion and plasma concentration of some gastrointestinal hormones in response to abomasal infusion of starch hydrolyzate and/or casein1

Abstract: Eight Angus steers (290 +/- 8 kg), surgically prepared with pancreatic pouch-duodenal reentrant cannulas and abomasal infusion catheters were used in a replicated 4 x 4 Latin square experiment to investigate the effects of abomasal infusion of starch hydrolyzate (SH) and/or casein on pancreatic exocrine secretion and plasma concentration of hormones. Steers were fed a basal diet of alfalfa (1.2 x NEm) in 12 equal portions daily. Abomasal infusion treatments (6-L total volume infused per day) were water (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 32 publications
6
41
0
2
Order By: Relevance
“…The CCK secretion in response to fatty acids and proteins increases pancreatic protease levels and activity in the small intestine of rats (Hara et al, 2000). Further, there are many reports on the connection between increased blood plasma CCK in response to protein injection into the small intestine and regulation of secretion in the exocrine gland of the pancreas (Tachibana et al, 1995; Swanson et al, 2004). Therefore, our results demonstrated that an increase in duodenal CCK and secretin levels upon oral administration of IC increased pancreatic α-amylase secretion.…”
Section: Resultsmentioning
confidence: 99%
“…The CCK secretion in response to fatty acids and proteins increases pancreatic protease levels and activity in the small intestine of rats (Hara et al, 2000). Further, there are many reports on the connection between increased blood plasma CCK in response to protein injection into the small intestine and regulation of secretion in the exocrine gland of the pancreas (Tachibana et al, 1995; Swanson et al, 2004). Therefore, our results demonstrated that an increase in duodenal CCK and secretin levels upon oral administration of IC increased pancreatic α-amylase secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is hypothesized that phenylalanine may also regulate PES by stimulating CCK secretion in ruminants. However, previous reports have shown that luminal protein decreases α‐amylase secretion in non‐ruminants (Brannon, 1990) and increases α‐amylase secretion in ruminants (Richards et al., 2003; Swanson et al., 2004), which indicates that regulation of nutrient factors on PES may have species differences. Therefore, it can be speculated that phenylalanine has different effects on PES in ruminants from that in non‐ruminants.…”
Section: Introductionmentioning
confidence: 87%
“…Responses to dietary or post-ruminal infusion treatment has been variable and inconsistent. Although the total content of pancreatic trypsin activity has been shown to increase with plane of nutrition (Wang et al 1998) and dietary CP concentration (Swanson et al 2008a), neither post-ruminal casein infusion (Richards et al 2003;Swanson et al 2004), post-ruminal partially hydrolyzed starch infusion (Swanson et al 2004), or different dietary protein sources (Khorasani et al 1990) have been observed to influence pancreatic secretion of trypsin activity. In the current experiment, although there were linear decreases in the concentration and content of trypsin activity with increasing corn silage inclusion, there were also significant cubic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although the total pancreatic content of active trypsin has been reported to increase with plane of nutrition (Wang et al 1998) or dietary crude protein (CP) concentration (Swanson et al 2008a), neither postruminal casein infusion (Richards et al 2003;Swanson et al 2004), post-ruminal partially hydrolyzed starch infusion (Swanson et al 2004) or different dietary protein sources (Khorasani et al 1990) have been observed to influence pancreatic secretion of active trypsin.…”
Section: Mots Clé Smentioning
confidence: 99%
See 1 more Smart Citation